PLASTIC BLANKETS AS TEMPERATURE STABILIZER FOR PREMATURE LOW BIRTH WEIGHT (LBW) BABY - Sunandar, Sendy Andrela; Aisah, Siti (Universitas Airlangga, 2024)
Introduction: Low birth weight (LBW) babies born via deep transperitoneal cesarean section (SCTP) with a gestational age of less than 34 weeks are highly susceptible to hypothermia. Hypothermia poses a significant risk of neonatal mortality, with LBW being one of the contributing factors. Thus, it is crucial to implement strategies to minimize heat loss and provide warmth, such as using plastic blankets. This case study aims to present the outcomes of implementing plastic blankets to manage hypothermia in LBW babies post-SCTP in the IBS Room at RSUP Dr. Kariadi Semarang. Methods: The study employs a descriptive design with a nursing care approach. The subjects included premature babies born via SCTP < 34 weeks. Three infant patients according to the criteria were included in the study. The measurement tool used was an observation sheet to monitor axillary temperature. The intervention plan involved providing plastic blankets to all three subjects to prevent hypothermia. Following birth, the infants were placed in an infant warmer, cleaned of mucus, wrapped in a plastic bag with a cloth cap on the head, underwent neonate resuscitation, and then covered with cloth while awaiting transfer to the room. Results: The findings indicate that the plastic blanket intervention increased the post-SCTP LBW temperature by an average of 0.50°C based on thermometer measurements and an average increase of 0.48°C based on infant warmer measurements. Conclusions: Therefore, it is recommended that healthcare professionals, particularly perinatology nurses, consider employing the plastic blanket method in managing hypothermia in LBW babies post-SCTP to maintain thermoregulation.